2021
DOI: 10.1158/1078-0432.ccr-21-0002
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of Cell-Free HBV Integrations and Mutations in Cirrhosis and Hepatocellular Carcinoma Patients

Abstract: Purpose: Intratumoral hepatitis B virus (HBV) integrations and mutations are related to hepatocellular carcinoma (HCC) progression. Circulating cell-free DNA (cfDNA) has shown itself as a powerful noninvasive biomarker for cancer. However, the HBV integration and mutation landscape on cfDNA remains unclear. Experimental Design: A cSMART (Circulating Single-Molecule Amplification and Resequencing Technology)-based method (SIM)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…Recently, the study of Zheng et al. has used paired samples to draw the landscape of VISs and VMs in HBV-associated cirrhosis and hepatocellular carcinoma ( 28 ). Our work will contribute to and help researchers who are interested in gene regulation mechanisms to systematically investigate the functional annotation of VISs in the host genome.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the study of Zheng et al. has used paired samples to draw the landscape of VISs and VMs in HBV-associated cirrhosis and hepatocellular carcinoma ( 28 ). Our work will contribute to and help researchers who are interested in gene regulation mechanisms to systematically investigate the functional annotation of VISs in the host genome.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…An understanding of viral pathogenic mutations and extraction of feature patterns mined from virus sequence data will improve effective surveillance and early detection for high-risk virus-infected diseases ( 25 , 26 ). Significant viral mutations/regions for affecting integration reactions ( 10 , 11 , 13 , 27 ) and the comparative analysis of virus integration/mutation landscapes at cfDNA level and paired tissues ( 28 ) have been reported. Previous studies have also demonstrated that transcriptional regulators contribute to the control of viral replication and regulate critical cis-elements in a virus ( 29 , 30 ).…”
Section: Introductionmentioning
confidence: 99%
“… 48 Notably, the number of HBV integration events in cfDNA of HCC patients is correlated with ctDNA concentration. 49 The plasma level of virus–host chimera DNA generated by HBV integration into the human genome is associated positively with tumor size. Therefore, HBV integration detected in cfDNA could be a circulating biomarker for prognostic prediction before tumor resection as well as monitoring residual or recurrent tumor after resection.…”
Section: Molecular Landscapes Of Ctdna In Hccmentioning
confidence: 99%
“… 58 For HBV integration, most of the mismatch breakpoints were regarded as random and sporadic events, except TERT and KMT2B breakpoints, which showed high concordance between HCC tissue and plasma cfDNA. 49 …”
Section: Consistency Between Plasma and Tumor Tissue In Hccmentioning
confidence: 99%
See 1 more Smart Citation